Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.21037/tau-22-709
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy of roxadustat and erythropoietin for the treatment of renal anemia in patients with chronic kidney disease: a retrospective study

Abstract: Background: Renal anemia is a common complication in patients with end-stage renal disease (ESRD).Both roxadustat and recombinant human erythropoietin (rhEPO) are alternative option for patients with renal anemia. However, the adverse events of rhEPO limited the wide use of it and the concrete difference of real clinical efficacy of rhEPO and roxadustat was still uncertain. This study aimed to assess the clinical efficacy of roxadustat for improving renal anemia in patients with chronic kidney disease.Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Anemia is a common complication of CKD caused by impaired oxygen sensing during renal failure. [ 14 ] As a HIF prolyl hydroxylase inhibitor, the novel agent roxadustat may increase endogenous erythropoietin concentrations by regulating the HIF, which is activated via the inhibition of certain activated domains. [ 15 ] In our study, roxadustat demonstrated prospective efficacy for the treatment of CKD patients with anemia, the Hb level after roxadustat treatment was significantly higher than the baseline value, and the iron metabolism-related indicators were significantly improved, which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia is a common complication of CKD caused by impaired oxygen sensing during renal failure. [ 14 ] As a HIF prolyl hydroxylase inhibitor, the novel agent roxadustat may increase endogenous erythropoietin concentrations by regulating the HIF, which is activated via the inhibition of certain activated domains. [ 15 ] In our study, roxadustat demonstrated prospective efficacy for the treatment of CKD patients with anemia, the Hb level after roxadustat treatment was significantly higher than the baseline value, and the iron metabolism-related indicators were significantly improved, which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Rinsing is the only way to eliminate creatinine because the body can't absorb or use it again. This means plasma creatinine concentrations show how well the kidneys filter waste, and high creatinine levels make the kidneys less effective (Jin et al, 2024).…”
Section: Discussionmentioning
confidence: 99%
“…The worldwide prevalence of chronic kidney disease (CKD) is increasing. In China, there are an estimated 120 million patients with CKD and approximately 2% will progress to end-stage renal disease (ESRD) ( 1 , 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…ESA hyporesponsiveness is associated with higher mortality rates and poorer clinical outcomes. The anemia must be corrected effectively, which often requires higher doses of rhuEPO, leading to a higher incidence of treatment-related adverse events, such as tumors, elevated blood pressure, endocrine system dysfunction, stroke, and cardiovascular events ( 2 , 7 15 ). Although it remains unclear whether adverse effect prognoses are a result of the direct toxicity of ESA or of underlying conditions requiring high doses of ESA ( 15 ), we should limit the dosage to a suitable range, which can increase the HB concentration without increasing the risk of side effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation